Direct one-pot synthesis of poly(ionic liquid) nanogels by cobalt-mediated radical cross-linking copolymerization in organic or aqueous media. Issue 14 (17th March 2016) - Weiss-Maurin, Mathilde; Cordella, Daniela; Jérôme, Christine; Taton, Daniel; Detrembleur, Christophe
Abstract : Nanogels of controlled kinetic chain length were synthesized by cobalt-mediated radical cross-linking copolymerization (CMRccP) involving a vinyl monomer and a divinyl cross-linker. Abstract : Nanogels of controlled kinetic chain length were synthesized by cobalt-mediated radical cross-linking copolymerization (CMRccP) involving a vinyl monomer and a divinyl cross-linker. This strategy was first validated to achieve neutral poly(vinyl acetate) nanogels by CMRccP of vinyl acetate and divinyl adipate as a cross-linker at 40 °C in the presence of an alkyl-cobalt(iii ) serving both as an initiator and a controlling agent using ethyl acetate as a solvent. Poly(ionic liquid) nanogels were then directly obtained by CMRccP of N -vinyl-3-ethyl imidazolium bromide in the presence of 1, 13-divinyl-3-decyl diimidazolium bromide as a cross-linker. CMRccP experiments could be conducted either in an organic solvent using dimethyl formamide or, more interestingly, in aqueous solution, demonstrating the robustness and versatility of this one-step process. Chain extensions of PIL nanogels were also carried out in water, forming core–shell structures, thus opening new avenues in the design of functional nanogels.